Association between abnormal Yolk Sac Appearance and early spontaneous Abortion. A Cohort study. - geddoa, salam abdulsahib (Karbala Journal of Medicine, 2020)
Abstract The yolk sac is essential in early life of the embryo because the yolk sac is the first route of exchange between the embryo and the mother. OBJECTIVE: To determine the association of the spontaneous abortion with the abnormal morphology and size of the yolk sac . .METHODS: A cohort study was conducted among 85 pregnant women aged 18-42 years with gestational age ranged between 7-12 wks, transvaginal U/S were done for all patients at first time. The gestational age was measured according to the LMP, CRL, MGSD and the difference between them (MGSD – CRL ). Then we divided the sample into two groups, study group which had abnormal yolk sac and control group with normal yolk sac. Then we followed the women for the 20th weeks of pregnancy and compared the spontaneous abortion rate between the two groups. RESULTS: Most of the embryos had a yolk sac with a regular shape (80%), whereas the remaining embryos had a yolk sac with an irregular shape (15%), calcified 2.5%. and 2.5% echogenic. about one third of the women with abnormal yolk sac ( cohort group ) had abortion in front of 10.9 % of the control group and the association was significant ( p value = 0.013). Significant association between spontaneous abortion and abnormal large diameter yolk sac. CONCLUSIONS: Abnormal yolk sac increased significantly risk for spontaneous abortion. Key words: spontaneous abortion, yolk sac, abnormal.